Mastery of Scientific Argumentation on the Concept of Neutralization in Chemistry: A Malaysian Perspective - Lee, Ling Heng; Surif, Johari; Cher, Hau Seng; Ibrahim, Nor Hasniza (Universiti Utara Malaysia Press, 2015)
Purpose - Argumentative practices are central to science education, and have recently been emphasised to promote students' reasoning skills and to develop student's understanding of scientific concepts. This study examines the mastery of scientific argumentation, based on the concept of neutralisation, among secondary level science students, when engaged in individual and group argumentations. Methodology - 356 form four science students were first randomly assigned to an argumentative condition, after their lesson on acids and bases, presented using the developed instructional materials. Each individual or group was then asked to answer an Open-ended Scientific Argumentation Test (OSAT). Discussions during group argumentations were observed and recorded. All the answers provided in the OSAT were then analysed based on their accuracy, the triplet relationship in chemistry and for the presence of argumentation elements. Observations from the group argumentations were transcribed and assessed. Findings - The results show that in both argumentative conditions, most of the arguments constructed tend to consist of the elements of claim and evidence. The results also show that students who work in groups outperform students who work individually. As individuals, most of the arguments presented tend to be simple with reasoning at a macro-level. As groups, the arguments presented are more complex, where justifications are provided at the sub-micro and symbolic levels, and with fewer misconceptions. That is because group argumentation participants have the opportunity to share ideas, detect and correct each other's mistakes, seek explanations and explain ideas. Significance - The study implies that group argumentation enhances students' argumentation and reasoning skills and improves their mastery of scientific concepts. In addition, this study also investigates students' performance from the Malaysian perspective.